Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Pertumbuhan Laba Pada Industri Makanan Dan Minuman Di Bursa Efek Indonesia Periode 2013-2017 - Nurdiana Nurdiana (Universitas Batanghari Jambi, 2019)
Effect of Cash Turnover, Receivable Turnover and Inventory Turnover on Profit Growth in the Food and Beverage Industries Listed on the Indonesia Stock Exchange Period 2013-2107 / Adisetiawan, SE.MM as I and Mufidah supervisors, SE.M.Si as second supervisor. This researcher aims to find out how the influence of cash turnover, accounts receivable turnover, and inventory turnover on profit growth both simultaneously and partially, this researcher takes the object of the food and beverage industry listed on the IDX for the period 2013-2017. The sample selection uses purposive sampling. The analytical method used is descriptive descriptive analysis method. The analytical tool in this study is the classic assumption test, multiple linear analysis with panel data, and hypothesis testing. This researcher was conducted in the food and beverage industry which consisted of PT. Wilmar Cahaya Indonesian Tbk, PT. Indofood CBP Sukses Makmur Tbk, PT. Indofood Sukses Makmur Tbk, PT. Siantat Top Tbk, PT. Nippon Indosari Corpindo Tbk, PT. Ultrajaya Milk Industry & Tranding Company Tbk, PT. Delta Djakarta Tbk. From the calculation using SPSS 21, the results of this study indicate cash turnover (XI), accounts receivable turnover (X2) and inventory turnover (X3) that affect earnings growth (Y) as seen in table F (4,679> 2.91) partially, Accounts receivable turnover and inventory turnover have a significant negative effect on earnings growth. The results showed that the data used in this study fulfilled the classical assumptions which included: data were normally distributed, there were no symptoms of multicollinearity, no symptoms of heteroscedacity, and autocorrelation did not occur. Simultaneously there is a significant effect on earnings growth, partially cash turnover variables affect the Y variable, while accounts receivable turnover and inventory turnover do not affect the variable Y.